Genetic Diversity and Evolutionary Biology of Indian Wildlife- A Review - Banerjee, Mainak; Kamble, Jayshree; Gautam, Saransh Kumar; KS, Aneesh; Bhure, Dhanraj Balbhim; Sadineni, Tejaswini; Kumar, G. Sadaya (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The genetic diversity and evolutionary biology of Indian wildlife, emphasizing the critical role of genetic variability in ensuring species adaptability and long-term survival. India is one of the world’s megadiverse countries, home to a wide range of unique flora and fauna spread across its biodiversity hotspots, including the Western Ghats and the Eastern Himalayas. However, rapid habitat fragmentation, deforestation, and poaching have severely impacted the genetic health of many wildlife species, leading to reduced gene flow, population bottlenecks, and increased inbreeding. This has heightened the risk of extinction for small, isolated populations such as the Asiatic lion and the Great Indian bustard. Genetic studies using advanced genomic tools have provided key insights into the population structure, phylogenetic relationships, and adaptive potential of species like the Bengal tiger, Asian elephant, and snow leopard. Conservation strategies, including genetic rescue, habitat corridors, and the use of captive breeding programs, are recommended to preserve genetic diversity and prevent further genetic erosion. Technological advances, such as non-invasive sampling and bioinformatics, are transforming wildlife research, enabling more precise and less intrusive genetic monitoring. The integration of genetic data into conservation policies and practices is essential for developing targeted management plans that maintain the evolutionary potential of Indian wildlife.